INST OX‐05‐024: first line gemcitabine, oxaliplatin, and erlotinib for primary hepatocellular carcinoma and bile duct cancers: a multicenter Phase II trial. (11th August 2017) - Patt, Yehuda Z.; Murad, Waheed; Fekrazad, Mohammed H.; Baron, Ari D.; Bansal, Pranshu; Boumber, Yanis; Steinberg, Kim; Lee, Sang‐Joon; Bedrick, Ed; Du, Ruofei; Lee, Fa Chyi
Abstract: Hepatocellular Carcinoma (HCC) incidence is increasing in the USA. Gemcitabine (G) and oxaliplatin (O) are active in HCC and biliary duct cancer (BDC). Erlotinib (E) is an EGFR tyrosine kinase inhibitor (TKI) with known activity against both. We sought to evaluate the efficacy of the combination G+O+E. Patients with either of the two diagnosis were treated in a phase II trial. Simons 2 stage design was used. A disease‐control rate (DCR), complete response (CR) + partial response (PR)+ stable disease (SD) at 24 weeks of ≤20% and >40% (P0 and P1 of 0.2 and 0.4, respectively) were set as undesirable (null) and desirable results. 26 HCC and 7 BDC patients were accrued. In HCC, 1 PR, 10 SD, and 9 PDs were seen. DCR in HCC was 42%. Among seven (7) patients with BDC, one patient was not evaluable; one achieved a long lasting PR, and five patients had SD and DCR was 86%. Median overall survival (OS) times and progression‐free survivals (PFS) were 196 and 149 days in HCC and 238 days and not reached in BDC. PFS at 26 weeks in HCC was 41% and at 21 weeks in BDC was 60%. Grade 3 toxicities in >5% of patients were fatigue (12.9%), neutropenia (9.6%), thrombocytopenia (9.6%), and diarrhea (6.4%). G+O+E exceeded both preset P0a and P1 of the primary objective with a PFS of 41% at 26 weeks for HCC and preliminary BDC data may warrant further investigations. Abstract : This is a phase II trial in the first line setting with gemcitabine, oxaliplatin, and erlotinib for primary hepatocellular carcinoma and bile duct cancer. The trial shows interesting results specially in the bile duct cancer arm and this combination should be tested in a randomized setting in comparison with standard of care.